Liquid chromatography coupled with time-of-flight and ion trap mass spectrometry for qualitative analysis of herbal medicines - Xiao-Fei Chen; Hai-Tang Wu; Guang-Guo Tan; Zhen-Yu Zhu; Yi-Feng Chai (Elsevier, 2011)
With the expansion of herbal medicine (HM) market, the issue on how to apply up-to-date analytical tools on qualitative analysis of HMs to assure their quality, safety and efficacy has been arousing great attention. Due to its inherent characteristics of accurate mass measurements and multiple stages analysis, the integrated strategy of liquid chromatography (LC) coupled with time-of-ï¬ight mass spectrometry (TOF-MS) and ion trap mass spectrometry (IT-MS) is well-suited to be performed as qualitative analysis tool in this field. The purpose of this review is to provide an overview on the potential of this integrated strategy, including the review of general features of LC-IT-MS and LC-TOF-MS, the advantages of their combination, the common procedures for structure elucidation, the potential of LC-hybrid-IT-TOF/MS and also the summary and discussion of the applications of the integrated strategy for HM qualitative analysis (2006â2011). The advantages and future developments of LC coupled with IT and TOF-MS are highlighted. Keywords: High-performance liquid chromatography (HPLC), Time-of-flight mass spectrometry (TOF-MS), Ion trap mass spectrometry (IT-MS), Herbal medicine (HM)